2006
DOI: 10.1128/aac.50.2.498-504.2006
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections Caused by Extended-Spectrum-β-Lactamase-Producing Klebsiella pneumoniae : Risk Factors, Molecular Epidemiology, and Clinical Outcome

Abstract: Bloodstream infections caused by extended-spectrum-␤-lactamase (ESBL)-producing Klebsiella pneumoniae isolates are a major concern for clinicians, since they markedly increase the rates of treatment failure and death. One hundred forty-seven patients with K. pneumoniae bloodstream infections were identified over a 5-year period (January 1999 to December 2003). The production of ESBLs in bloodstream isolates was evaluated by molecular methods. A retrospective case-case-control study was conducted to identify ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
211
3
26

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(249 citation statements)
references
References 42 publications
9
211
3
26
Order By: Relevance
“…17 For this reason, it is important to clarify these issues for the design of strategies aimed at reducing resistances. Other variables associated with the identification of ESBL-producing strains in patients with bloodstream infection reported in the literature are the patient's age, 15 severe underlying diseases, 13 renal transplantation, 13 previous admission to the ICU, 18 duration of hospitalization before bacteremia, 19 prior exposure to urinary catheters, 10,14,16 invasive procedure within the previous 72 hours, 16 and the nosocomial origin of bacteremia. 10 In a systematic review of studies evaluating the association between inappropriate antibiotic therapy and mortality among bacteremic patients, measurement of severity of illness without specified the time at which it was measured was considered a source of methodological heterogeneity that may explain conflicting findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 For this reason, it is important to clarify these issues for the design of strategies aimed at reducing resistances. Other variables associated with the identification of ESBL-producing strains in patients with bloodstream infection reported in the literature are the patient's age, 15 severe underlying diseases, 13 renal transplantation, 13 previous admission to the ICU, 18 duration of hospitalization before bacteremia, 19 prior exposure to urinary catheters, 10,14,16 invasive procedure within the previous 72 hours, 16 and the nosocomial origin of bacteremia. 10 In a systematic review of studies evaluating the association between inappropriate antibiotic therapy and mortality among bacteremic patients, measurement of severity of illness without specified the time at which it was measured was considered a source of methodological heterogeneity that may explain conflicting findings.…”
mentioning
confidence: 99%
“…14 Other studies, however, have found an association between previous exposure to antimicrobials in general and identification of ESBL-producing strains in patients with bacteremia caused by K. pneumoniae. 15 In a retrospective case-control study in patients with K. pneumoniae bacteremia, for the addition of each antimicrobial agent, an increase of 1.55 in the risk of ESBL-producing K. pneumoniae strains was observed. 16 Although a large number of studies included in their objectives to assess the association between use of antibiotics and the emergence of resistance, the systems used to define the prior use of antimicrobials have not been properly Risk factors for bloodstream infections caused by ESBL-producing Escherichia coli and Klebsiella pneumoniae described.…”
mentioning
confidence: 99%
“…Gram-negative bacilli accounted for 19% of catheter-associated BSIs during 1986-1989 [32], compared with 14% during 1992-1999 [33]. An increasing percentage of intensive care unit-related isolates are extended-spectrum β-lactamase-producing Enterobacteriaceae, particularly Klebsiella pneumoniae [34]. A c c e p t e d M a n u s c r i p t faecium, 7% of E. faecalis); P. aeruginosa resistant to ceftazidime and quinolones, or piperacillin, or carbapenems (30%, 17% and 25%, respectively).…”
Section: Page 9 Of 42mentioning
confidence: 99%
“…Unlike S. aureus CRBSI [34] secondary enterococcal endocarditis appears to be a rare complication, but if the patient has signs and symptoms of endocarditis, persistent bacteraemia or enterococcal bacteraemia in the presence of a prosthetic valve a transoesophageal echocardiograph should be done [59,63]. The IDSA guidelines for the treatment of enterococcal CRBSI caused by susceptible isolates advise either ampicillin or vancomycin alone or in combination with an aminoglycoside [39], as data concerning the role of combination therapy for treatment If a long-term catheter is retained in cases of uncomplicated infection 7-14 days of intravenous treatment is recommended in addition to antibiotic lock therapy [64].…”
Section: Enterococcus Sppmentioning
confidence: 99%
“…In a study from South Korea, ESBL-associated bacteremia was identified as an independent risk for mortality in patients with hematologic malignancies and associated with a 30-day mortality of almost 45 % [28]. Although many ESBLs produced by E. coli are inhibited by β-lactamase inhibitors such as tazobactam, piperacillin is not consistently active and carbapenems remain the treatment of choice for ESBL-related infections; delay of early adequate antibiotic therapy still correlates with increased mortality outcomes [25,[29][30][31]. Unfortunately, frequent co-carriage of other antibiotic resistance genes on ESBL-expressing plasmids has led to increasing multidrug resistance including the fluoroquinolones [32].…”
Section: Epidemiology Of Resistant Gram-negative Bacterial Infectionsmentioning
confidence: 99%